On COVID-19 diffusion in Italy: data analysis and possible outcome - Fabiano, Nicola; Radenović, Stojan (Vojnotehnički glasnik / Military Technical Courier, 2020)
Introduction/purpose: At the end of 2019, the Coronavirus disease 2019 (COVID-19) was identified  first in the Hubei province of China and then it spread over the world causing the coronavirus pandemic. The virus has given very different outcomes in different countries up to day - at the time of writing, Italy has a record number of deaths caused by coronavirus (Google, 2020).Methods: A mathematical model is applied to describe the behavior of number of cases with respect to time, the obtained data is compared and some predictions given.Results: The model chosen to represent the evolution of the spread of the disease allows making some projections for the future.Conclusions: Sound projections could be created with accurate numbers provided the current situation is not perturbed by other external influences.
Keywords: Coronavirus; COVID-19; differential equation; data fit